A revision of the Eudarcia glaseri-species group (Lepidoptera, Meessiidae) with description of two new species from Greece and Crimea - Bidzilya, Oleksiy V.; Budashkin, Yury I.; Gaedike, Reinhard (Zootaxa, 2016)
The Eudarcia glaseri-species group is revised. Four species are recognized, two of which are described as new: E. ignorata, sp. n. (Greece) and E. saxatilis, sp. n. (Crimea). E. abchasicum (Zagulajev, 1979) status rev., bona sp. is recalled from synonymy of E. glaseri. Re-descriptions and an identification key for all four species are given. The hitherto unknown females of E. glaseri (Petersen, 1967) and E. armatum (Gaedike, 1985) are described.